2011
DOI: 10.3923/pjbs.2011.496.501
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically-Assisted vs. Open Surgery in Repairing Anterior Cruciate Ligament Avulsion

Abstract: The management of an Anterior Cruciate Ligament (ACL) avulsion is principally by surgery. There are two major techniques in this regard; fixation through open surgery (arthrotomy) or arthroscopically-assisted repair. These are not new in the literature; however, the debate regarding the better approach is still under debate. This study focused on comparing outcome and consequences of arthroscopically-assisted vs. open surgery in repairing ACL avulsion. In a randomized clinical trial, 44 patients with unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In some previous studies, Frank and Jackson [ 5 ] reported that arthroscopic reconstruction has better functional outcome in short-term but the outcomes were similar to open procedures in long-term. However, Barzegar et al [ 6 ] reported arthroscopic reconstruction is superior to a mini arthrotomy procedures in time taken to return to pre-injury working level. There are only few studies comparing arthroscopic procedure with an open procedure as arthroscopy offers minimally invasive and more cosmetic surgery and have overshadowed open procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In some previous studies, Frank and Jackson [ 5 ] reported that arthroscopic reconstruction has better functional outcome in short-term but the outcomes were similar to open procedures in long-term. However, Barzegar et al [ 6 ] reported arthroscopic reconstruction is superior to a mini arthrotomy procedures in time taken to return to pre-injury working level. There are only few studies comparing arthroscopic procedure with an open procedure as arthroscopy offers minimally invasive and more cosmetic surgery and have overshadowed open procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Cyril b Frank (10) reported that arthroscopic reconstruction has a better functional outcome in the short term but the outcomes are not significantly different in the long term. But Hamid Barzegar (11) reported arthroscopic reconstruction is superior to a mini arthrotomy procedure in the time taken to return to pre-injury working level.…”
Section: Discussionmentioning
confidence: 99%
“…Open ACL reconstruction and arthroscopic reconstruction are not new as lots of literature is available about these two but the debate regarding which approach is better is still going on. 9 In this retrospective analysis, our objective was to compare LKS scores following ACL reconstruction and arthroscopic reconstruction, and comparing with each other.…”
Section: Discussionmentioning
confidence: 99%